An overview on the effect of pumping on concrete properties. (May 2022) - Li, Fumin; Shen, Wenkai; Yuan, Qiang; Hu, Xiang; Li, Zhuguo; Shi, Caijun
Abstract: Pumping is a widely used placement means for concrete construction, but both fresh and hardened property changes in concrete due to pumping. In this review, the effects of pumping on both the fresh and hardened properties of various concrete mixtures are presented in terms of each specific characteristic. Analyses of data from the published literature showed that the air content of fresh concrete is altered after pumping. The general trend in the change in rheological properties of fresh concrete due to pumping was also determined, and the mechanisms of this trend were discussed. Moreover, the improvement in the compressive strength of hardened concrete was investigated, which is considered to result from the pumping-induced hydration acceleration and the air content variation. Finally, changes in the durability of hardened concrete were discussed, and future research topics were suggested.